Awareness and perceptions of social development employees regarding employee health and wellness program at Lepelle-Nkumpi Municipality - Mphahlele, Kamogelo Maditsi (My University, 2019)
Employee Health and Wellness Program is an intervention to form a comprehensive health, productivity, risk management and wellness in the workplace. The study was therefore aimed at assessing awareness and perceptions by social development employees of the Employee Health and Wellness Program. Descriptive crosssectional quantitative research was conducted using a self-administered questionnaire. Inclusion criteria was implemented to select study respondents, and of 102 study population, 66 employees fulfilled the inclusion criteria. The findings revealed that 77% of the respondents had negative perceptions of the program and 72.7% of respondents were less aware of the program. Contributing factor to negative perceptions and less awareness of the program is unclear. However, it could relate to location and marketing of the program as it is centralised at district offices. The services of health and wellness coordinators and peer educators at local municipal levels were recommended for promotion and marketing. Keywords: Awareness, Perception, Social development employees, Employee Health and Wellness Program.
Thesis (MPH.) -- University of Limpopo, 2019
Keywords: Awareness; Perception; Social development employees; Employee Health and Wellness Program; Health services administration -- Employee participation; Health facilities -- Employees; Employee health promotion